Microempresa de consumo masivo en el Recinto El Progreso - Changoluisa Cunuhay, Wilson Enrique (2017)
The project was developed with the purpose of solving the problems that the inhabitants of recinto "El Progreso" precinct have, the greatest difficulty is to access sources of financing and not being willing to give prominence when starting a new business, these are the main causes that have generated that this area presents lack of a well organized microenterprise that can provide an optimal service and a wide variety of products of mass consumption; Causing the residents to move to other sites to make purchases, generating unnecessary costs of transportation and mainly of time, among others. Looking for an alternative solution to the problems detected we proposed a feasibility study to create a microenterprise dedicated to promote this type of products in the recinto “El Progreso”. For the project, descriptive research methods were used which allowed analyzing the reality of the problem described above, the analytical method allowed to gather information necessary for the development of the project, the same that was analyzed and refined to carry out a measurement of the acceptance of the proposal; Bibliographical research was also used. With the obtained information, the analysis of the supply and demand was carried out, determining an unsatisfied demand of 684,696 units of food products, among which are: rice, soda, milk, chicken meat and toothpaste, these values allowed to establish that there is a market for the implementation of the proposal. The technical study determined that the project will require the initial investment of $ 160,437.85 and the financial study reflected profits of $ 29,528.73 for the year 2016, a NPV of $ 62,804.72 and a 29% IRR. The microenterprise will provide its services in the rural area of the town “Pujilí”, benefiting the inhabitants of the area.